Correlates of HIV Testing Among Rural African American Cocaine Users. Issue 6 (25th October 2014) - Wright, Patricia B.; Booth, Brenda M.; Curran, Geoffrey M.; Borders, Tyrone F.; Ounpraseuth, Songthip T.; Stewart, Katharine E.
Abstract Andersen's Revised Behavioral Model of Health Services Use (RBM) was used as a framework in this correlational cross‐sectional study to examine factors associated with HIV testing among a sample of 251 rural African American cocaine users. All participants reported using cocaine and being sexually active within the past 30 days. Independent variables were categorized according to the RBM as predisposing, enabling, need, or health behavior factors. Number of times tested for HIV (never, one time, two to four times, five or more times) was the outcome of interest. In ordered logistic regression analyses, HIV testing was strongly associated with being female, of younger age (predisposing factors); having been tested for sexually transmitted diseases or hepatitis, ever having been incarcerated in jail or prison (enabling factors); and having had one sex partner the past 30 days (health behavior factor). Other sexual risk behaviors, drug use, health status, and perception of risk were not associated with HIV testing. Our findings confirm the importance of routine testing in all healthcare settings rather than risk‐based testing. © 2014 Wiley Periodicals, Inc.